1994
DOI: 10.1080/10587259408046919
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of an Intercalated Structure in a Smectic A Phase

Abstract: The destruction of the intercalated smectic A structure of a laterally bulky branched 1,4-phenylen dibenzoate A by addition of a rodlike cinnamate B was studied by the phase diagram as well as by calorimetric. x-ray and dielectric measurements. The thermal stability of the S, phase of compound A and its phase transition enthalpy decrease with increasing concentration of B. Furthermore, the destruction of the short range order of A is characterized by increasing layer distances, decreasing dipolar correlation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Berdague, et al (1993) reported new laterally aromatic branched liquid crystal (LC) materials with the N and S m C phases. In another study done by Haddawi, et al (1994) about the lateral aryl substituents, the synthesized compound shows the N and S m A phases. Aziz (2000) synthesize some new Schiff-base-diester compounds, during this study, the mesomorphic behavior of the Schiff-base compounds shows the N, S m C, and S m I mesophases ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Berdague, et al (1993) reported new laterally aromatic branched liquid crystal (LC) materials with the N and S m C phases. In another study done by Haddawi, et al (1994) about the lateral aryl substituents, the synthesized compound shows the N and S m A phases. Aziz (2000) synthesize some new Schiff-base-diester compounds, during this study, the mesomorphic behavior of the Schiff-base compounds shows the N, S m C, and S m I mesophases ( Fig.…”
Section: Introductionmentioning
confidence: 99%